(untitled) (El-Wahat Journal for Research and Studies, 2015)
This study deals with the subject of performance in the market of mobile telephony in Algeria. Indeed, the latter is a component of great interest for large economic enterprises and one of the key factors that determine their success. We focused in this study on the overall performance of the mobile industry saw its leading role as one of the prerequisites for each industry and its impact on industrial structure and strategies adopted by companies belonging to the sector. To evaluate performance, we opted for the choice of the three following indicators: profitability, the growth of certain economic indicators and technical progress. At the end of our study, it was observed a rapid growth in some economic indicators such as market share and turnover, as well as constantly growing profitability rate. We also noted the low level of technology in this sector and which does not meet the expectations of customers in particular with regard to services provided to businesses and businessmen. Despite the current situation of the sector, the indicators mentioned above constitute factors of attraction for companies that want to invest in this industry like Orange and Vodafone. Keywords: performance, business strategy, information technology and communication, profitability, the mobile phone market, the industry structure ,.